Sustainable management of food waste in federal universities: a documentary analysis of strategies in Brazilian Southeast (Research, Society and Development, 2020)
Due to increased consumption and inadequate waste disposal, causing environmental damage for present and future generations, it is necessary to change from a linear economy to a circular economy, where what is “garbage” in a production process becomes matter press on the other. This article aims to identify strategies used for the management of food waste in university restaurants, in Brazilian public higher education institutions. A sample of 19 federal universities in southeastern Brazil was chosen. The data on the management of food waste residues from these institutions were collected in the Institutional Development Plans, Sustainable Logistics Plans and the Institutions website. The research showed that despite 73.68% of the sample talking about waste in their Institutional Development Plan and or Sustainable Logistics Plan, only three universities disclose on their websites information about treatments and / or research carried out by them in the scope of waste management food. The data indicate the need to weave institutional policies and strategies for the theme.